Geographic opportunistic routing protocol based on two-hop information for wireless sensor networks. (7th May 2019) - ; Achar, L. Akshay; Kushal, P.; Venugopal, K.R.
To improve energy efficiency and packet delivery ratio in WSNs. We propose a two-hop geographic opportunistic routing ( THGOR ) protocol that selects a subset of 2-hop neighbours of node which have higher packet reception ratio and residual energy as the next forwarder node, it also selects 1-hop neighbours that have excellent coverage of 2-hop neighbours as relay nodes. The proposed protocol is compared with geographic opportunistic routing ( GOR ) and efficient QoS-aware geographic opportunistic (EQGOR). GOR and EQGOR select a forwarding sensor node on the basis of distance. However, GOR and EQGOR results in lower packet delivery rate, and quick depletion of energy. The THGOR is comprehensively evaluated through NS-2 and compared results with EQGOR and GOR. Simulation results show that THGOR significant improvement in packet advancement, reliable transmission, energy efficiency and optimises packet transmission delay.